Exploring the circular business model for sustainable plastic waste management in shopping malls: Challenges, opportunities, and impacts in Thailand - Pavinee Pongpunpurt; Nattawin Chawaloesphonsiya; Thaksina Poyai; Pascal Guiraud; Ligia Tiruta-Barna; Rapeeporn Rungsithong; Unruan Leknoi; Dao Janjaroen; Pisut Painmanakul (Case Studies in Chemical and Environmental Engineering)
This study addresses the significant contribution of shopping malls to plastic waste management by assessing alternatives that balance environmental and economic impacts. Data were collected through a mixed-methods approach (in-depth interviews and questionnaires) and analyzed using the thematic analysis. The research highlights the pivotal role of policymakers in fostering collaborations essential for effective plastic waste management. A novel business model centered on resource recovery is proposed based on the analysis of the plastic waste landscape from both macro-factors and key stakeholders' perspectives. Due to the enhancement in plastic recycling rates, this model could reduce greenhouse gas emissions by up to 19.88 tCO2-eq per year and generate an annual revenue of USD 584. The findings advocate for collaborative efforts between mall stores and office spaces to increase the availability of recyclable plastics. The outcomes contribute to the formulation of evidence-based environmental policies tailored to shopping malls, promoting sustainable solutions aligned with circular economy principles and offering a framework that can be adopted by stakeholders across the plastic ecosystem.